2023
DOI: 10.1111/jfd.13795
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genetic characterization of Saprolegnia parasitica, isolated from farmed and wild fish in Finland

Abstract: Oomycete infections in farmed fish are one of the most significant disease issues in salmonid aquaculture worldwide. In the present study, Saprolegnia spp. in different farmed fish species in Finland were identified, and the molecular epidemiology of especially Saprolegnia parasitica was examined. We analysed tissue samples from suspected oomycete‐infected salmonids of different life stages from a number of fish farms, as well as three wild salmonids. From collected oomycete isolates, the ITS1, 5.8S and ITS2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…australis and S . ferax are often found in water samples [ 7 , 20 , 34 36 ], thus the new species could be still considered potential pathogen. Nevertheless, further in vivo experiments are required to understand if S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…australis and S . ferax are often found in water samples [ 7 , 20 , 34 36 ], thus the new species could be still considered potential pathogen. Nevertheless, further in vivo experiments are required to understand if S .…”
Section: Discussionmentioning
confidence: 99%
“…n. was isolated from water sample, thus we cannot draw any conclusions regarding its pathogenicity yet. The most common fish pathogen species, S. parasitica, or the known saprotrophs damaging fish eggs, such as S. australis and S. ferax are often found in water samples [7,20,[34][35][36], thus the new species could be still considered potential pathogen. Nevertheless, further in vivo experiments are required to understand if S. velencensis sp.…”
Section: Discussionmentioning
confidence: 99%
“…(2011, 2015) in Norway isolated S. diclina and S. parasitica predominantly from Salmo salar eggs, while S. ferax and S. hypogyna were usually isolated from adult Salmo salar fish. Recent studies in Finland have showed that, as in Lithuania, about 90% of affected salmonid fish in Finnish fish farms were infected with S. parasitica , especially at the post‐hatching stage, whereas S. diclina was usually favoured eggs (Engblom et al., 2023). Other fish pathogens from aquaculture in Finland included S. australis , S. diclina , S. torulosa , Saprolegnia sp.…”
Section: Discussionmentioning
confidence: 99%
“…ferax and S. hypogyna were usually isolated from adult Salmo salar fish. Recent studies in Finland have showed that, as in Lithuania, about 90% of affected salmonid fish in Finnish fish farms were infected with S. parasitica, especially at the post-hatching stage, whereas S. diclina was usually favoured eggs (Engblom et al, 2023).…”
Section: F I G U R E 8 Saprolegniasis Infectionmentioning
confidence: 99%
See 1 more Smart Citation